2018
DOI: 10.1128/iai.00297-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Acinetobacter baumannii Type VI Secretion System Antibacterial Effector and Immunity Pairs

Abstract: The type VI secretion system (T6SS) is a macromolecular machine that delivers protein effectors into host cells and/or competing bacteria. The effectors may be delivered as noncovalently bound cargo of T6SS needle proteins (VgrG/Hcp/PAAR) or as C-terminal extensions of these proteins. Many strains produce a T6SS, but little is known about the specific effectors or how they are delivered. In this study, we show that AB307-0294 encodes three loci, each containing a gene, a T6SS toxic effector gene, and an antito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 70 publications
(97 reference statements)
5
95
0
Order By: Relevance
“…8), the DUF2345 domain may require additional elements present at the C terminus of VgrG for proper function. Moreover, a recent bioinformatic analysis of 73 VgrGs across 22 A. baumannii strains, as well as the soil bacterium A. baylyi ADP1, showed that all VgrGs contain a DUF2345 domain (58). The high levels of conservation suggest that the It is noteworthy that our results are not in conflict with previous results indicating that the C terminus of VgrG is dispensable for T6SS function (52,53).…”
Section: Downloaded Fromsupporting
confidence: 43%
See 1 more Smart Citation
“…8), the DUF2345 domain may require additional elements present at the C terminus of VgrG for proper function. Moreover, a recent bioinformatic analysis of 73 VgrGs across 22 A. baumannii strains, as well as the soil bacterium A. baylyi ADP1, showed that all VgrGs contain a DUF2345 domain (58). The high levels of conservation suggest that the It is noteworthy that our results are not in conflict with previous results indicating that the C terminus of VgrG is dispensable for T6SS function (52,53).…”
Section: Downloaded Fromsupporting
confidence: 43%
“…Given that we identified no differences in the predicted functional domains of canonical VgrGs and those of VgrGi, we reasoned that VgrGi may possess critical differences in its primary sequence that are responsible for its inhibitory ability. VgrGs encoded by A. baumannii strains were recently grouped into six distinct phylogenetic groups (58). Based on the amino acid identity (Ͼ95%), we determined that VgrGi belongs to class 1 VgrGs.…”
Section: Resultsmentioning
confidence: 99%
“…brasiliense strain PBR 1692 (Bellieny-Rabelo et al, 2019) but no nuclease activity has been tested. In Acinetobacter baylyi, it was shown that the genomic DNA was completely degraded when Rhs2 with C-terminal AHH motif is expressed in E. coli (Fitzsimons et al, 2018). In this study, we characterize further to show that the AHH motif is indeed responsible for the DNase activity ( Figure 5).…”
Section: Discussionmentioning
confidence: 72%
“…Regarding virulence factors, A. baumannii usually encodes a type VI secretion system (T6SS), which can be used to kill competitors (Weber et al, 2013). It is likely that the presence of this system may be associated to the survival in the nosocomial niche (Fitzsimons et al, 2018). Here, we searched the genes coding for the proteins critical for T6SS operation (Weber et al, 2016;Repizo et al, 2019) in Groups 1, 2, 3 and 4, as well as tetR1 and tetR2 repressors in Groups 1, 2 and 3 ( Supplementary Table 13).…”
Section: In Vitro Competition Of A144 and A155mentioning
confidence: 99%